A Social Interactionist Approach to the Victim-Offender Overlap - Berg, Mark T. (Journal of quantitative criminology, 2020)
A social interactionist perspective suggests that violent offenders are frequently victims of violence because of the way they behave, and the way third parties behave during verbal disputes that lead to escalation. We examine to what extent violent offenders are more likely to be victimized because they tend to engage in provocative actions, are less likely to engage in remedial actions, and more likely to be intoxicated, and because third-parties have a greater tendency to encourage aggressive behaviors during disputes involving offenders.